Where is the consumer centre? A case of St. Petersburg - Konstantin Kholodilin; Irina Koroleva; Darya Kryutchenko (Regional Science Policy & Practice, 2020)
In an urban economy, the distribution of people and real estate prices depends on the location of the central business district of a city. As distance from the city centre increases, both prices and population density diminish, for travel costs increase in terms of time and money. As manufacturing gradually leaves the cities, the importance of consumer amenities as attractors of population to the urban areas increases. The role of a business centre is being replaced by the consumer centre. In this paper, we identify the location of the consumer centre of St. Petersburg — the second largest city in Russia and its former capital. For this purpose using the data from open sources in the Internet regarding the location of many different types of urban amenities, the indices of their spatial density are computed. Using the weights based on coefficients of spatial variation and survey-based weights, the individual indices are aggregated to two general centrality indices. Their unique maxima correspond to the city centre of St. Petersburg, which is located on Nevsky prospekt, between Fontanka river and Liteinyi prospekt.
Keywords: 320; St. Petersburg; urban amenities; consumer city centre; 2D kernel density estimation